Status quo bias and public policy: evidence in the context of carbon mitigation. (13th May 2021) - Lang, Corey; Weir, Michael; Pearson-Merkowitz, Shanna
Abstract: This article examines whether individuals' preferences for government policy are affected by status quo bias. We designed a contingent valuation survey that asks respondents directly about their willingness to pay (WTP) for their state to be a part of a regional carbon mitigation policy. The survey has two randomized frames, which differ in whether or not their state is already part of the policy. We distributed the survey to a representative sample of Rhode Island residents ( N = 844). We find that respondents who believe that Rhode Island would be joining the policy for the first time have a WTP to join of 170 (quite similar to previous research at a national scale), whereas those who believe Rhode Island is already part of the policy are willing to pay 2.5 times more, or 420, to stay in the program. Our results suggest that citizens greatly prefer existing carbon mitigation policies to new policies, which implies that carbon policy will be more successful if enacted through the legislature instead of popular vote.